Rancang Bangun Dashboard Untuk Visualisasi Produktivitas Bahan Baku Tebu Pada Pabrik Gula Gempolkrep - Welly Abdi Prayogi; Henry Bambang Setyawan; Anjik Sukmaaji (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Pabrik Gula Gempolkrep is one of the subsidiaries of PTPN X engaged in the production of sugar. Currently Pabrik Gula Gempolkrep already using sistem informasi pabrik gula(SIPG) to support business processes, information systems used but still can not help pabrik gula gempolkrep to monitoring the productivity of sugarcane feedstock. This needs to be rectified as to achieve production targets. Pabrik Gula Gempolkrep need to monitor the productivity of sugarcane raw material that becomes the main raw material in sugar production. Based on the above, it was built dashboard for visualization of raw material productivity of sugarcane in Pabrik Gula Gempolkrep. The dashboard is designed to meet the information needs of sugarcane productivity of the manajer tanaman and kepala tebang angkut. The results of the evaluation system productivity dashboard for visualization of the raw material sugar cane in the mill Gempolkrep can change the raw material sugar cane productivity data into visual information that is accurate and in accordance with user needs to monitor the achievement of the productivity of sugarcane feedstock.Keywords: Dashboard, Visualization, Productivity